The effectiveness of communicative function of the text in learning a language (Eurasian Journal of Philology Science and Education, 2016)
The article deals with theoretical research of the text in linguistics and with positive influence of the text as a linguistic unit on learning and teaching a language. The article also considers the effectiveness of teaching a language using the communicative function of the text and effectiveness of used methods. The article contains the analysis of the role of the text in enriching the vocabulary and in developing the communicative ability of a learner. Not only reading and analyzing of the text but also expressing learners’ points of view and critical approach towards the text broadens learners’ horizon on teaching a language. The effective methods used in working on the text are given in the article. There is also an analysis of effective use of the communicative function of the text given in the article. The article also deals with ways of constructive teaching with the help of the text as a result of reproductive method.
Keywords: text; work on the text; communicative function of the text; vocabulary; communicative theory of the text